2010
DOI: 10.1007/s10750-010-0213-z
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Nemopsis bachei L. Agassiz, 1849 medusae in the presence of physical gradients and biological thin layers

Abstract: In pelagic systems, thin layers (discontinuities with narrow vertical extents and high concentrations of organisms) create patches of food, and aggregations of gelatinous zooplankton can exploit such resources. The establishment, maintenance, and trophic effects of these functional relationships depend on behavioral responses to thin layers by individuals, which remain largely unexplored. In this study, we used laboratory experiments to test the hypothesis that a common and abundant hydromedusa predator, Nemop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 63 publications
1
8
0
3
Order By: Relevance
“…1). Those locations are known for chronic summertime hypoxia in previous years (Keister et al 2000, Breitburg et al 2003 , was calculated as the difference between adjacent depths in seawater density (σ t ), as calculated from T and S using a seawater density calculator (Tomczak 2000), based on Fofonoff & Millard (1983). Although sampling was necessarily at discrete depths, all variables form continuous gradients in the field.…”
Section: Sample Collection and Analysesmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Those locations are known for chronic summertime hypoxia in previous years (Keister et al 2000, Breitburg et al 2003 , was calculated as the difference between adjacent depths in seawater density (σ t ), as calculated from T and S using a seawater density calculator (Tomczak 2000), based on Fofonoff & Millard (1983). Although sampling was necessarily at discrete depths, all variables form continuous gradients in the field.…”
Section: Sample Collection and Analysesmentioning
confidence: 99%
“…Graham et al 2001, Jacobsen & Norrbin 2009), the possible importance of density discontinuities and stratification per se must be considered. Both Arai (1992) and Frost et al (2010) concluded that hydromedusae behaviorally aggregate at salinity discontinuities. Aurelia sp.…”
Section: Vertical Distributions Of Ctenophores Medusae and Copepodsmentioning
confidence: 99%
See 3 more Smart Citations